Antibiotic resistome biomarkers and determinants in lettuce planting soil amended with β-lactam pharmaceutical fermentation residues - Ruiqi Wan; Kaixuan Zheng; Tianyu Chen; Yanping Xun; Jitao Lv; Lingyi Meng; Yufei Yang; Xuemei Zhu (Bioresource Technology, 2027)

Numerical analysis of downwash airflow distribution from multi-rotor UAV in soybean-maize strip intercropping canopy - Xinghua Liu; Lei Yang; Yang Li; Zhi Li; Fan Jiang; Yanping Tian; Xiang-Dong Li (Biosystems Engineering, 2026)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

Study on dynamic response and damage mechanism of tunnel across reverse fault based on different earthquake action modes - Rui Sun; Xiaojun Li; Yanping Yang; Ren Deng; Teng Li; Dingding Xiong (Tunnelling and Underground Space Technology, 2026)

LORE-mediated engineering of enhanced bacterial resistance in Solanaceous crops - Meng Wang; Qing Shan; Xiaohui Yang; Yanping Tian; Bo Zhou; Dan Wen; Biao Gong (Journal of Plant Physiology, 2026)

Plasma technology regulated In3S4 nanosheets surface cationic defects enhanced photocatalytic H2O2 production in pure water - Fei Li; Yang Zhang; Yongjie Zhou; Yanping Gao; Longkai Pan; Chen Sun; Hequn Yang; Fei Rao; Gangqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Long-term PFOA and cadmium Co-contamination alters soil carbon, nitrogen, and phosphorus cycling: Insights from metagenomics and metabolomics - Yanping Cai; Beihai Zhou; Shuming Liu; Chuyu Shang; Baoguo Yang; Yunqing Liu; Shengguang Zhang; Ruixue Fan; Waseem Hassan; Rongfang Yuan; Huilun Chen (Environmental Research, 2026)

Spatial heterogeneity of humic acids- and nitrate-driven anaerobic oxidation of methane mediated by ANME-2d in paddy soils - Yanan Bai; Lei Dai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Zhaozhong Feng (Applied Soil Ecology, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Upcycling waste glass into chitosan-modified zeolite for heavy metal immobilization and deep mineralization: A "waste-treats-waste" paradigm - Xinxin Li; Rongxin Guo; Zhihan Zhang; Yifeng Zou; Ziyi Yang; Dexun Zou; Yanping Liu (Process Safety and Environmental Protection, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Integrated transcriptomics and lipidomics provide insights into the stage-specific antifungal mechanisms of eugenol against Fusarium graminearum - Xin Yang; Luzhou Cai; Yueling Luo; Lianqun Wu; Xinyue Wang; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2026)

Cooling load forecasting for urban district cooling systems using a hybrid multi-scale deep learning approach - Chao Zeng; Yang Feng; Haixia Cao; Jing Wang; Yanping Yuan (Energy and Buildings, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Pomelo polysaccharides: A review of the extraction techniques, purification, structural characteristics, interactions, biological activities, applications and future prospects - Jingwei Wang; Ting Yang; Kaiyang Liu; Yuesong Xiao; Xiaoming Wang; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Sustained activation of peracetic acid by hydroxylamine and ferrous irons for enhanced short-chain fatty acids production from sludge fermentation - Guilin Ma; Yanping Zhang; Jing Zhang; Kun Yang; Shuyu Yang (Journal of Water Process Engineering, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Response mechanisms of enhanced biological phosphorus removal systems to microplastics stress - Mingwan Yang; Li Tian; Qihao Li; Guijie Li; Lulu Dai; Anni Du; Liguan Li; Ke Yu; Yanping Mao (Journal of Hazardous Materials, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Integrated Application of Iso-Seq and RNA-Seq Analyses to Uncover Genes Involved in Ovarian Development in Platypharodon extremus - Zhuoyu Yang; Yanping Zhang; Wei Ka; Wenjing He; Yujie Yang; Wenlong Jiao; Jianlin Wang (Fishes, 2026)
This study focused on Platypharodon extremus, a species endemic to the Qinghai–Tibet Plateau, and systematically analyzed its reproductive biology, sex steroid hormones, ovarian histology, and transcriptomic characteristics throughout its complete reproductive cycle (August 2020 to June 2021). The results demonstrated that the body length, height, body weight, and gonadal weight of female individuals continuously increased with age, while the Gonadosomatic index (GSI) was lowest during the breeding season (June–August) and gradually rose during the non-breeding period. Serum estradiol (E2) and progesterone (P4) exhibited rhythmic fluctuations corresponding to ovarian development: E2 rose from 25.77 ng/L in stage-I to 146.00 ng/L in stage-V, then declined post-ovulation; P4 increased from 59.88 pmol/L in stage-I to 239.03 pmol/L in stage-V, showing a significant decrease after ovulation. Histological observations classified ovarian development into stages I–VI, clearly delineating the complete process from oogonium proliferation, cortical vesicle formation, yolk accumulation, maturation to postpartum regression. To explore molecular changes during the transition from vitellogenesis to oocyte maturation, we built a reference transcriptome with 30,060 non-redundant transcripts (average length = 1975 bp) using PacBio and Illumina data, and 91.87% of these transcripts received functional annotation hits against public databases. A comparative differential expression analysis was performed between ovarian stage III (active yolk accumulation) and stage V (oocyte fully matured). A total of 11,324 differentially expressed genes were identified (5249 upregulated and 6175 downregulated) between these two stages. GO enrichment analysis revealed predominant involvement in cellular processes, cellular components, and catalytic activities, while KEGG analysis demonstrated significant enrichment in metabolic pathways, PI3K-Akt, MAPK, and calcium signaling pathways. Quantitative PCR (qPCR) validation confirmed that candidate genes, including pik3a, calm, mapk1 map2k ddx49, and igf2 were significantly upregulated at stage V. These differentially expressed genes (DEGs) may represent potential molecular signatures linked to the transition from vitellogenesis to oocyte maturation. Our integrated transcriptomic and qPCR data identify potential gene candidates involved in ovarian maturation; however, these findings reveal correlation rather than direct regulatory causality. This study offers fundamental data and theoretical insights for understanding the reproductive regulatory mechanisms and aquaculture management of this endemic species.

RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

Urinary volatile organic compound metabolites and depressive symptoms among U.S. adults with cardiovascular-kidney-metabolic syndrome stages 0–3: NHANES-based associations and in silico multi-omics insights - Yulin Tian; Yiyun Wang; Hongsi Cui; Hongjie Wang; Yanping Yang; Yu Chang (NeuroToxicology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

Urban Cooling Island Dynamics During the Development of an Ecological Urban Agglomeration in China - Ziwu Pan; Zunyi Xie; Lifei Huang; Fen Qin; Minmin Yu; Shuyu Yang; Zihan Wang; Jinyuan Han; Zenyan Wang; Yanping Cao; Zhihua Shi; Cangyu Li (Chinese Geographical Science, 2026)

Decline of beneficial microbes and proliferation of latent pathogens: Key drivers of postharvest disease in citrus - Jianghua Chen; Mengting Xu; Ting Zhu; Ziyi Yang; Juan Liu; Jie Duan; Yang Lin; Xiao Yu; Daohong Jiang; Yanping Fu (Postharvest Biology and Technology, 2026)

Explainable daily warning of algal concentration exceedance from SHAP-guided temperature and light thresholds - Dawei Xu; Yanping Hu; Shouye Yang; Lu Wang; Long Wang (Journal of Environmental Chemical Engineering, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Boosting electrochemical performance of aqueous zinc-ion batteries with high-coulombic-efficiency Zn anodes stabilized by PEG/CMC-Na crosslinked networks - Duanyi Jiang; Yanping Yang; Yanwen Zhu; Huiqin Zhang; Xiaoyan Qiu; Haizhou Yu (Chemical Engineering Journal, 2026)

Integrative metabolomic and transcriptomic analyses reveal coordinated variation in phenolic acid metabolism and redox-related traits in Ocimum basilicum accessions - Jingtian Yang; Zhengqiao Liao; Jialin Li; Mei Liu; Yanping Mao; Guoyu Yang; Lei Liu (Planta, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Novel Hybrid Peptide ML-2 with Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa - Shenghua Wu; Yanping Shi; Yang He; Tao Zhang; Feilong Chen; Yingchun Zhang; Tao Wang (Current Microbiology, 2026)

AutoML democratizes water quality forecasting: Lowering expertise barriers - Yangyang Chu; Yun Fang; Liangzhi Sun; Yang Zhang; Liujian Wang; XiaoMeng Han; Mou Lv; Haixing Liu; Kunlun Xin; Weigang Wang; Yanping Zhu; Shihu Shu (Journal of Water Process Engineering, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

The dual role of humic acids in driving anaerobic oxidation of methane in paddy soils - Dehong Yang; Yanping Wang; Yuanhao Lan; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

The atmospheric residual error model of time-series InSAR based on ERA-5 PWV in Beijing, China - Haozhe Chi; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Fei Qiao; Xiangshun Meng; Chunhong Liu; Yanping Liu (Advances in Space Research, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

GhDREB1B-GhFAD3-2 module mediates drought tolerance by regulating linolenic acid biosynthesis in cotton - Yufei Liang; Luqi Wang; Yuxin Yang; Ronggui Yu; Yanping Shi; Liyong Hou; Xin Zhou; Yan Zhang; Guanghui Xiao (Science China Life Sciences, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Analysis of atmospheric residual error and construction of correction model for GACOS-Corrected PS+DS time-series InSAR based on ERA5 PWV - Fei Qiao; Yong Wang; Yunlong Zhang; Chen Chang; Haozhe Chi; Chunhong Liu; Xiangshun Meng; Yanping Liu; Chengwu Yang (International Journal of Remote Sensing, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

Transcriptome analysis of possible genetic-level defects in the use of large-sized Chinese mitten crab ( Eriocheir sinensis ) parents for breeding - Fujun Xuan; Jinghao Hu; Lei Gao; Ruifang Wang; Yanping Yang; Ying Pan; Jun Zhou; Rongchen Liu (Invertebrate Reproduction & Development, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Chronological and geochemical constraints on the origin and timing of carbonate-cemented sandstones in the Middle Jurassic Zhiluo Formation, northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Yanping Ma; Lihua Yang; Nan Du (Marine and Petroleum Geology, 2025)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Improvement of electron transfer via anthraquinone-2-sulfonate addition to enhance volatile fatty acids production in anaerobic digestion system - Xiaoyue Li; Tingting Jiang; Huiyan Jing; Yue Cui; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2025)

Research on hourly precipitation prediction along railways based on ERA5 reanalysis and post-processing correction - Xiangshun Meng; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Haozhe Chi; Yanping Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Environmentally relevant low metal concentrations drive co-selection of antibiotic and metal resistance genes in activated sludge - Li Tian; Guijie Li; Liguan Li; Mingwan Yang; Huixin Li; Qihao Li; Yanping Mao (Environmental Research, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

A potent and selective PROTAC degrader of CDK9 as effective inhibitor of HIV-1 RNA synthesis - Bo Yang; Ling Ma; Xiaotang Yang; Jiajia Wen; Weiyi Yin; Siqi Li; Yingjie Ji; Ying Wang; Shan Cen; Yanping Li (Molecular Diversity, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Unraveling the alkaloid diversity and pharmacological potential of Ocimum: Integrated UPLC-MS/MS, network pharmacology, and transcriptomic insights for functional food and drug discovery - Jingtian Yang; Jing Yuan; Mengling Yu; Yanping Mao; Mei Liu; Lingliang Guan; Lei Liu (Food Research International, 2025)

Valorizing industrial and agricultural wastes into a high-performance composite for remediation of heavy metal-contaminated tailing sands - Mengjia Liang; Man Xue; Yanping Shi; Jihua Cai; Xianyu Yang; Chunzheng Jin; Zexin Chen; Maoyan Xu (Environmental Research, 2025)

Ru/S-modified hollow ZIF-67 for efficient sulfapyridine degradation via enhanced PMS-AOPs and inhibited of cobalt leaching - Zhuoqun Deng; Zhiyi Fan; Changchun Si; Jia Zhu; Ziyi Yang; Dexun Zou; Yanping Liu (Chemical Engineering Journal, 2025)

Analysis of human electroencephalogram features in hypobaric oxygen-enriched environments - Mingxi Yang; Xuanyuan Gou; Liangliang Sun; Xiaowen Su; Yanping Yuan (Building and Environment, 2025)

A multivariate framework for assessing propagation thresholds from meteorological to hydrological drought across indus river Basins-South Asia - Irfan Ullah; Xin-Min Zeng; Sidra Syed; Jiefeng Wu; Xiaoye Yang; Shadab Syed; Ning Wang; Yanping Li (Stochastic Environmental Research and Risk Assessment, 2025)

High-resolution profiling observation of carbon source dynamics in a mussel farm in the Changjiang River estuary during early autumn - Dawei Xu; Di Wu; Shouye Yang; Yanping Hu; Kui Wang (Journal of Oceanology and Limnology, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

Insights into stress response pathways and potential triterpene accumulation mechanisms induced by friction damage in kiwifruit - Fan Yang; Yuchun Wang; Fangzhi Wu; Sike Wang; Yuduan Ding; Yue Chen; Qinggang Zhu; Yanping Ma (Postharvest Biology and Technology, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Effects of inorganic salt ions on long-term retrogradation characteristics of lotus seed starch under microwave treatment - Yingting Zhao; Zhiyang Lu; Yang Liu; Yanping Lei; Yuting Tian (Food Hydrocolloids, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Resveratrol inhibits autophagy in cardiomyocytes subjected anoxia/reoxygenation injury: involved in VDAC1/PINK1/Parkin pathway - Ying Zhou; Yongzhe Huang; Haiyan Liang; Xiaomei Yang; Shulin Zhang; Yinru Huang; Yanping Wan; Hangfei Zhou; An Huang; Yue Chen; Xiao Li; Yian Peng; et al. (Toxicology and Applied Pharmacology, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Development of tissue culture techniques and comparative metabolomics for Echeveria ‘Pretty in Pink’ calli - Shuangbin Fu; Zhen Ying; Chaoxiang Chen; Yanping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Corrosion characteristics of low-carbon cast steel ZG230-450 in chloride-sulfate atmospheric environment - Xuan Zheng; Yanping Zhao; Hongxin Yang; Baorong Liu; Chi Zhang (Environmental Science and Pollution Research, 2025)

Enhanced therapeutic efficacy of Dioscorea cirrhosa Lour. n -butanol fractions in ulcerative colitis: a dual administration approach with comprehensive mucosal protection and anti-inflammatory effects - Mei Wang; XingJu Peng; CanJiao Yang; XinLong Yu; HaiChuan Tai; YanPing Li (Natural Product Research, 2025)

Energy saving and carbon reduction benefits of ventilated photovoltaic walls combined with non-balanced thermal insulation in Lhasa residential buildings - Xinrong Zhu; Daijun Huang; Yanyan Niu; Yan Liu; Yanping Yuan; Liu Yang; Jiaping Liu (Energy and Buildings, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

Impact of microplastics on plant biogenic volatile organic compounds emission: A preliminary study - Shuqin Liu; Shengmei Feng; Yanping Zhang; Yang Zheng; Ruifen Jiang; Gangfeng Ouyang (Journal of Hazardous Materials, 2025)

Transcriptomics and Metabolomics Analysis Reveal the Mechanism of Hormones Regulation of the Flower Bud Formation and Development in Phalaenopsis Orchid - Xiaofen Gao; Yang Hao; Xiaoying Yang; Yanping Shi; Li Zhang; Rui Yan (Journal of Plant Growth Regulation, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Synthesizing ZIF-8 functionalized biochar by in situ reuse of residual Zn from chemical activation for enhanced tetracycline hydrochloride adsorption removal - Jianying Liu; Qian Zeng; Yao Chen; Zhongde Dai; Wenju Jiang; Lu Yao; Junfeng Zheng; Dengrong Sun; Yanping Wu; Lin Yang (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

An advanced numerical model for dynamic daylight and energy consumption analysis of thermal-responsive complex fenestration system with adaptive solar absorption - Yang Ming; Mingke Hu; Xiao Liu; Yanping Yuan; Yupeng Wu (Energy and Buildings, 2025)

Comprehensive impact of two advanced thermotropic façades designs on building daylight and energy performance - Yang Ming; Fujian Jiang; Cemil Alkan; Yanping Yuan; Yupeng Wu (Energy and Buildings, 2025)

Paracoccus yibinensis sp. nov., a novel bacterium with astaxanthin producing isolated from the environment of Chinese distilled Baijiu - Qingchun Luo; Yanping Lu; Xi Li; Jian Su; Pengju Zhao; Zhu Zhang; Yang Gu; Dong Zhao; Jia Zheng (Antonie van Leeuwenhoek, 2025)

Influencing Factors on Oyster Recruitment and Performance Evaluation for Oyster Reef Restoration in Tianjin Coastal Zones - Yuxuan Zhao; Chen Yang; Bo Zhang; Yanping Li; Jianbo Tu; Fuxin Niu; Wenliang Kong; Zhiyun Wang; Xianhua Liu (Oceans, 2025)
Global oyster reefs have suffered severe degradation due to human activities, environmental pollution, and climate change. The construction of artificial reefs offers a promising strategy to enhance oyster recruitment and mitigate population decline. However, the factors influencing oyster recruitment in artificial frameworks remain largely unclear, and it is still challenging to evaluate the effectiveness of different restoration methods. In this study, a series of oyster reef restoration experiments were conducted in the Tianjin coastal zone to identify key factors affecting recruitment success. These factors included restoration methods (shell string, mesh bag, and mesh cage), seeding with juvenile oysters, oyster shell orientation, and cultch hanging height. Our results indicated that the mesh bag method achieved the highest oyster settlement density in the intertidal zone, while the shell string method supported the fastest growth rates of oysters in the subtidal zone. The lower hanging height of cultches in the artificial frames increased oyster settlement density; however, hanging the cultches too close to the sediment negatively impacted oyster growth rates. Additionally, seeding with juvenile oysters and orienting the rough side of the shell upward enhanced recruitment performance. Oyster settlement density was greater in the intertidal zone (Bagua Shoal) compared to the subtidal zone (Dashentang), while oysters in the subtidal zone exhibited faster growth rates. Using redundancy analysis, the influence of environmental factors on the oyster recruitment performance was assessed. Oyster growth in the subtidal zone was positively correlated with dissolved oxygen and pH, whereas oyster settlement density in the intertidal zone was positively associated with water temperature, chlorophyll a concentration, and salinity. Finally, we evaluated the effectiveness of different restoration methods by considering factors including reef construction costs, oyster settlement abundance, average daily shell growth rate, water purification potential, and reef subsidence. Our results demonstrated that the shell string method was the most effective in the Dashentang subtidal zone, while the mesh bag method with oyster seeding was optimal in the Bagua Shoal intertidal zone. Our findings can provide valuable insights and guidance for oyster reef restoration projects.

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Templating effect of monoglycerides in controlling the spatial distribution of solid fat crystals within double emulsions - Yanping Huang; Zengliu Song; Yang You; Yunqi Li; Tongfei Shi; Jie Xiao (Food Chemistry, 2025)

Comprehensive lipid profiling and metabolic pathway analysis of Ocimum: Unveiling key variations and regulatory mechanisms for breeding and metabolic exploration - Jingtian Yang; Chengting Zhang; Mengling Yu; Jing Yuan; Yanping Mao; Mei Liu; Lei Liu; Lingliang Guan (Food Bioscience, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

Monosome Stalls the Translation Process Mediated by IGF2BP in Arcuate Nucleus for Puberty Onset Delay - Yifen Shen; Le Zhang; Tao Yang; Xiaosong Li; Chao Liu; Hongmei Li; Yanping Hu; Hao Shen; Hua Li; Yuriy L. Orlov; Shasha Zhou; Yihang Shen (Molecular Neurobiology, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Identification and characterization of Morganella morganii strain YC12-C3 and Enterococcus faecalis strain YC12-C10 and elucidation of its deoxynivalenol-degrading potential - Jiuchun An; Yefei Chen; Shihua Zhou; Yanping Gao; Changgui Yang; Jinqiang Zhang; Xiaohong Ou; Yanhong Wang; Weike Jiang; Tao Zhou; Qing-Song Yuan (Mycotoxin Research, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Antibiofilm mechanism of 2R,3R-dihydromyricetin by targeting sortase A and its application against Staphylococcus aureus adhesion on eggshell - Wenyi Ran; Peirui Yi; Ling Jiang; Yang Yu; Kai Zhong; Yanping Wu; Hong Gao (International Journal of Food Microbiology, 2025)

Forest transformation increases soil N2O fluxes in an unmanaged Moso bamboo forest - Yibo Yan; Xueying Tu; Hui Zhang; Yang Lv; Yihui Zhao; Ao Hu; Yanping Wu; Caixian Tang; Yixiang Wang (Forest Ecology and Management, 2025)

Ultrafine Na3V2(PO4)3@C with boosted interfacial charge transfer kinetics for low-temperature (−40 °C) Na-ion battery - Yanjing Liu; Shitan Xu; Huacheng Zhu; Yang Yang; Yang Yang; Yanping Zhou; Xianhong Rui (Chemical Engineering Journal, 2025)

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

Climate change drives fish communities: Changing multiple facets of fish biodiversity in the Northwest Pacific Ocean - Shuhao Liu; Yang Liu; Qinwang Xing; Yuru Li; Hao Tian; Yanping Luo; Shin-ichi Ito; Yongjun Tian (Science of The Total Environment, 2024)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

Characteristics of volatile organic compounds under different operating conditions in a petrochemical industrial zone and their effects on ozone formation - Yanping Yang; Xianhong Meng; Qiang Chen; Qiang Xue; Lina Wang; Jian Sun; Wenkai Guo; Huijie Tao; Lili Yang; Feifei Chen (Environmental Pollution, 2024)

Effects of valley topography on ozone pollution in the Lanzhou valley: A numerical case study - Wenkai Guo; Yanping Yang; Junke Zhang; Keran Han; Yinhua Yang; Qiang Chen; Shixue Li; Yuhuan Zhu (Environmental Pollution, 2024)

Effect of rebar ratio, rebar diameter, cover thickness, and fiber shape on flexural and cracking behavior of rebar-reinforced UHPC beams - Minghong Qiu; Xudong Shao; Kay Wille; Yanping Zhu; Yan Wang; Yang Zhang; Zhenyu Tao (Engineering Structures, 2024)

Numerical investigation on effects of fuel rod with the position of bow deformation on the flow and heat transfer of PWR - Chengde Li; Mei Huang; Delong Sun; Xiaoping Ouyang; Yanping Huang; Yang Liu (Annals of Nuclear Energy, 2024)

A life cycle reliability testing and assessment method for deepwater oil and gas equipment systems - Chuntan Gao; Baoping Cai; Yanping Zhang; Xiaoyan Shao; Chao Yang; Lei Gao (Ocean Engineering, 2024)

Can combined wind and solar power meet the increased electricity load on heatwave days in China after the carbon emission peak? A case study in southern Hebei - Jie Bai; Mingxin Zhao; Xiaohui Qin; Yanping Xu; Yang Liu (Journal of Cleaner Production, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Two-stage hydrothermal liquefaction of Spirulina: Experimental observations, energy analysis and techno-economic assessment - Hongwei Pang; Yanping Feng; Xinru Ma; Qirong Yang; Zhaoying Li (Process Safety and Environmental Protection, 2024)

Upcycling of nutrients from kitchen waste: Integration of anaerobic digestion system and microbial protein production system - Qile Zhu; Kangjian Gao; Qi Sun; Chuan Ma; Yuxing Luo; Zijin Niu; Yanping Liu; Ziyi Yang (Journal of Environmental Management, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

The practice and innovation of compatible marine utilization models in China - Yanping Li; Yan Yang; Yuting Hou; Xiao Liu; Dahai Liu (Frontiers in Marine Science, 2024)
Marine Spatial Planning (MSP) is essential for optimizing marine resources allocation and resolving conflicts in sea use, but it is challenged by the complex and multi-functional nature of maritime resources. This study utilizes participatory methods, inductive reasoning, and overlay analysis to explore both theoretical and practical aspects of compatible marine utilization models. The paper begins by clarifying the logic of compatible sea use through marine functional zoning and identifying its core characteristics: quantity, spatial conflict, and impacts on natural attributes. Building on China’s national territorial spatial planning reforms and practical experiences, the paper introduces three major categories of compatible marine use models: development sequencing compatibility, spatial coexistence compatibility, and functional synergy compatibility. A compatibility discrimination matrix is developed to assess these models across different marine functional areas. Combined with the compatibility discrimination results, taking the marine and coastal spatial planning of Yantai City in China as a case study, the paper analyzes the compatibility demands and planning strategies within various marine functional areas. Finally, it evaluates the risks associated with each compatibility model and proposes targeted control strategies tailored to the specific features of each model and characteristics of sea use activities. The research findings highlight the positive role of compatible sea use models in promoting marine economic development, enhancing spatial efficiency, and mitigating sea use conflicts. However, these models also present varying potential risks, necessitating differentiated control strategies aligned with legal frameworks and specific sea use activities. The study offers valuable insights for MSP and contributes to the efficient utilization of marine resources and the advancement of marine spatial governance.

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

Exploring potential causal links between air pollutants and congenital malformations: A two-sample Mendelian Randomization study - Shufen Li; Yanping Zhang; Kaiyan Yang; Wenbo Zhou (Reproductive Toxicology, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

Enhanced ofloxacin degradation in water by a novel integrated photocatalysis and rotating magnetic field system - Ning Ding; Sijia Zhang; Jianxin Zhang; Yang Zhan; Bokang Wang; Hong Liu; Yanping Zhang; Yingxue Sun (Journal of Water Process Engineering, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Comparison of anaerobic co-digestion of vacuum toilet blackwater and kitchen waste under mesophilic and thermophilic conditions: Reactor performance, microbial response and metabolic pathway - Ziang Wang; Haixiang Li; Pingbo Wang; Jia Zhu; Ziyi Yang; Yanping Liu (Journal of Environmental Management, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Response of water quality in major tributaries to the difference of multi-scale landscape indicators in Dongting Lake basin, China - Yang Bai; Zhifei Ma; Yanping Wu; Hailin You; Jinying Xu (Environmental Science and Pollution Research, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Novel insight into the formation and improvement mechanism of physical property in fermented tilapia sausage by cooperative fermentation of newly isolated lactic acid bacteria based on microbial contribution - Qiaoyan Cui; Laihao Li; Hui Huang; Yanping Yang; Shengjun Chen; Chunsheng Li (Food Research International, 2024)

Rapid classification of coffee origin by combining mass spectrometry analysis of coffee aroma with deep learning - Huang Yang; Jiawen Ai; Yanping Zhu; Qinhao Shi; Quan Yu (Food Chemistry, 2024)

Evolution of runoff discharge patterns and risk assessment of water inrush in mountainous railroad tunnels - Xu Yang; Dandan You; Xin Gao; Qi Li; Xinhao Hu; Saixing Zeng; Jingxiao Zhang; Yanping Hu; Lanxin Kang (Natural Hazards, 2024)

Knocking out Selenium Binding Protein 1 Induces Depressive-Like Behavior in Mice - Yi Jia; Xin Zhang; Yongmei Wang; Yang Liu; Jie Dai; Liangliang Zhang; Xian Wu; Jie Zhang; Hongxi Xiang; Yanping Yang; Zhu Zeng; Yulian Chen (Biological Trace Element Research, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Quantitative evaluation and mechanism analysis of soil chemical factors affecting rice yield in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Xiaotong Jiang; Ying Liu; Guangzhi Huang; Can Yang; Yanping Liang; Jinghui Cai; Ge Zhu; Qianqian Kong (Science of The Total Environment, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Research on leaching behavior of manganese and ammonia nitrogen in electrolytic manganese residue under oxalic acid/hydrogen peroxide system - Chenxin Sun; Yu Zhang; Yanping Yang; Qian Shang; Yunqiu Liu; Qianlin Chen (Journal of Water Process Engineering, 2024)

Interaction mechanism of global multiple ocean-atmosphere coupled modes and their impacts on South and East Asian Monsoon: A review - Guiping Li; Zhongbo Yu; Yanping Li; Chuanguo Yang; Huanghe Gu; Jingwen Zhang; Ya Huang (Global and Planetary Change, 2024)

Multifunctional Ac@ZIF-8/AgNPs nanoplatform with pH-responsive and ROS scavenging antibacterial properties promotes infected wound healing - Yipeng Pang; Maofang Zhao; Yuhan Xie; Yanping Wang; Yuxin You; Yongding Ke; Chaoyi Zhang; Xiaohan Chen; Yijia Yang; Chunlei Zhang; Xi Chen; Yi Liu; et al. (Chemical Engineering Journal, 2024)

TCE degradation of modified graphite felt cathode in a flow-through electro-Fenton system and its H2O2 production ability in a real contaminated field - Yanping Cui; Haodong Yang; Xian Xiang; Shibo Zhao; Qiao Huang; Zhaoqiang Huang (Chemical Engineering Journal, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

D-Limonene Alleviates Oxidative Stress Injury of the Testis Induced by Arsenic in Rat - Yanping Yang; Yan Hong; Jing Han; Zhe Yang; Nanmin Huang; Binwei Xu; Qi Wang (Biological Trace Element Research, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Controlled atmosphere storage alleviates the browning of walnut (Juglans regia L.) fruit through enhancing GABA-mediated energy metabolism - Niu Ye; Dongli Zhang; Shan Liu; Yongqi Zhang; Yifan Wang; Yan Tang; Xiangna Yang; Jiahao Chai; Yanping Ma; Huiling Ma (Postharvest Biology and Technology, 2024)

Understanding the variable metal concentrations in estuarine oysters Crassostrea hongkongensis: A biokinetic analysis - Shaomei Yang; Yanping Li; Fengyuan Chen; Shanshan Chen; Xin Luo; Wei Duan; Yongyan Liao; Hao Jiang; Ke Pan (Marine Environmental Research, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Biochar co-pyrolyzed from peanut shells and maize straw improved soil biochemical properties, rice yield, and reduced cadmium mobilization and accumulation by rice: Biogeochemical investigations - Weijie Xu; Xiaocui Xie; Qi Li; Xing Yang; Jiajia Ren; Yanping Shi; Dan Liu; Sabry M. Shaheen; Jörg Rinklebe (Journal of Hazardous Materials, 2024)

High voltage, toughness and improved interfacial ion deposition through a dual-crosslinked and self-healable hydrogel electrolyte for green zinc-ion batteries - Yanping Yang; Luwei Shi; Yaqi Wu; Zhehua Chen; Xinyuan Zhu; Lijun Du; Youfu Wang (Chemical Engineering Journal, 2024)

Aquifer Water Abundance Evaluation Based on a Variable Weight Model - Aoshuang Mei; Qiang Wu; Keyao Han; Yifan Zeng; Pengfei Yang; Yanping Miao; Yang Lv; Yashuai Cui; Liang Yang (Mine Water and the Environment, 2024)

Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of Coilia nasus in the Yangtze River - Shuwei Wei; Zhong Hua; Yanping Yang; Fengjiao Ma; Wei Han; Wei Zhang; Congping Ying; Yanmin Deng; Kai Liu (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

Synthesis of defective Ni-Mn layered double hydroxides nanosheets via alkali-assisted Mo doping for urea electro-oxidation - Ming Yang; Wanyu Ge; Zirui Liu; Qiang Yue; Jun Zhang; Yanping Lv; Hao Wu (Fuel, 2024)

Understanding quality differences between kiwifruit varieties during softening - Fan Yang; Renkai Zhao; Jiangtao Suo; Yuduan Ding; Jiawei Tan; Qinggang Zhu; Yanping Ma (Food Chemistry, 2024)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Engineering redirected NF-κB/OIP5 expression programs to enhance tumor responses to chemotherapy in bladder cancer - Binbin Zheng; Liman Niu; Haibo Xu; Yubin Yang; Yanping Chen; Chenguang Wang; Wei Chen; Weiren Huang (Science Bulletin, 2023)

Gas-expanded pore MOF derived Sm/MnOx catalysts enable ultralow-temperature selective catalytic reduction of NOx - Shengchen Li; Dan Zhao; Shunli Shi; Fangyu Zhu; Yanping Yang; Shuhua Wang; Shunmin Ding; Chao Chen (Journal of Environmental Chemical Engineering, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

A mother-son model for multi-objective non-invasive load monitoring - Huawei Mei; Yanping Liu; Wangbin Cao; Yang Yu (Energy and Buildings, 2023)

Novel aloe emodin–hydroxyethyl piperazine hybrid dihydrochloride induces oral cancer CAL-27 cells apoptosis through ROS production, DNA damage and mitochondrial pathways - Xing Long; Peilin Yang; Lin Chen; Wen Zhong; Shaofeng Chen; Yanping Li; Shijie Lin; Wei Tian (Medicinal Chemistry Research, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

Efficient degradation of tetrabromobisphenol A using peroxymonosulfate oxidation activated by a novel nano-CuFe2O4@coconut shell biochar catalyst - Xinxin Li; Xujing Li; Chuang Song; Xiaojin Yang; Yanping Liu; Jia Zhu (Environmental Pollution, 2023)

Stream restoration can reduce nitrate levels in agricultural landscapes - Xiangqian Zhou; Seifeddine Jomaa; Xiaoqiang Yang; Ralf Merz; Yanping Wang; Michael Rode (Science of The Total Environment, 2023)

Adding the third component with similar building blocks to regulate the miscibility of active layer enables high efficient ternary solar cells - Shichu Peng; Jinxin Luo; Peng Li; Liangang Xiao; Chongqing Yang; Yaocheng Jin; Ruiying Lin; Yanping Huo; Yi Liu; Yonggang Min (Chemical Engineering Journal, 2023)

Biocrust and sand burial together promote annual herb community assembly in an arid sandy desert area - Yanhong Gao; Rongliang Jia; Yanping Liu; Yun Zhao; Yongshen Wu; Haotian Yang; Lichao Liu; Yulong Duan; Lina Zhao; Wanxue You (Plant and Soil, 2023)

Screening and optimization of a water-soluble near-infrared fluorescent probe for drug-induced liver injury monitoring - Yanping Pan; Qiuxing Yang; Hong Xu; Zhenwei Yuan; Hui Xu (Analytica Chimica Acta, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

Corn-straw-derived, pyridine-nitrogen-rich NCQDs modified Cu0.05Zn2.95In2S6 promoted directional electrons transfer and boosted adsorption and activation of CO2 for efficient photocatalytic reduction of CO2 to CO - Jinhang Yang; Yanping Hou; Jiangli Sun; Jingwen Wei; Shiming Zhang; Jiaxiang Liang; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Kinetic and thermodynamic analysis on preparation of belite-calcium sulphoaluminate cement using electrolytic manganese residue and barium slag by TGA - Weilong He; Rui Li; Yanping Yang; Yu Zhang; Dengpan Nie (Environmental Science and Pollution Research, 2023)

Influence of vehicle length on the aerothermodynamic environment of the Hyperloop - Yang Sui; Jiqiang Niu; Qiujun Yu; Xiaoling Cao; Yanping Yuan; Xiaofeng Yang (Tunnelling and Underground Space Technology, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Comparison of yield prediction models and estimation of the relative importance of main agronomic traits affecting rice yield formation in saline-sodic paddy fields - Baishun Liu; Ying Liu; Guangzhi Huang; Xiaotong Jiang; Yanping Liang; Can Yang; Lihua Huang (European Journal of Agronomy, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis - Wei Liu; Kailun Liu; Jiao Cai; Shuang Ma; Minghan Yang; Quan Yang; Yanping Yuan (Sustainable Cities and Society, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Microwave-carbon fiber cloth co-ignited catalytic degradation of waste plastic into high-yield hydrogen and carbon nanotubes - Bowen Zhang; Hui Wang; Yiyun Yang; Yanping Zhou; Bing Zhang; Kama Huang (Journal of Environmental Chemical Engineering, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

Impact of reinforcing ratio and fiber volume on flexural hardening behavior of steel reinforced UHPC beams - Yang Zhang; Yanping Zhu; Junfeng Qiu; Changgui Hou; Jinju Huang (Engineering Structures, 2023)

A double-glazed solar air-phase change material collector for nocturnal heating: Model development and sensitivity analysis - Li Yang; Nan Zhang; Yanping Yuan; Fariborz Haghighat; Mohamed Dardir; Karthik Panchabikesan; Qinrong Sun (Energy and Buildings, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Genetic Diversity and Population Structure Analysis of Chinese Mitten Crab (Eriocheir sinensis) in the Yangtze and Liaohe Rivers - Lin Zhou; Jiancao Gao; Yanping Yang; Zhijuan Nie; Kai Liu; Gangchun Xu (Fishes, 2023)
Recently, the economic traits of Chinese mitten crab (Eriocheir sinensis) varieties have had a negative tendency. Meanwhile, the status of wild germplasm resources of E. sinensis is unknown, hindering the utilization of wild germplasm resources and the green development of the E. sinensis industry. Thus, the conservation of the wild E. sinensis germplasm resource is of great significance. To this end, we collected wild E. sinensis from two different river basins, the Yangtze River basin, and the Liaohe River basin, and analyzed the genetic diversity as well as the genetic differentiation in E. sinensis populations. Based on eight microsatellite markers, we found moderate genetic diversity in E. sinensis populations regardless of river basin. Based on the mitochondrial D-loop region, we found that all populations are at mutation drift equilibrium, while the Nm between any two populations is greater than 1. We hypothesized the existence of island model gene flow patterns among E. sinensis. Interestingly, genetic differentiation among E. sinensis populations was low, except that between Liaohe and Anqing or Shanghai populations. Additionally, geometric morphological analysis could distinguish E. sinensis from different basins, with an accuracy of 94.2–100%. Given the similar genetic diversity in the two basins, the genetic convergence of E. sinensis from different basins deserves further attention.

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

The effect of in vitro digestion on the chemical and antioxidant properties of Lycium barbarum polysaccharides - Wenjun Zeng; Lulu Chen; Yanping Li; Jianlong Ma; Rui Yang; Jianbao Ding; Jin Yang (Food Hydrocolloids, 2023)

CFD simulation of a full-scale three-dimensional flow and temperature distribution inside a reactor under ocean conditions - Houjun Gong; Mengqi Wu; Nan Gui; Xingtuan Yang; Jiyuan Tu; Shengyao Jiang; Yanping Huang; Yuanfeng Zan (Annals of Nuclear Energy, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Insight into structural characteristics of theabrownin from Pingwu Fuzhuan brick tea and its hypolipidemic activity based on the in vivo zebrafish and in vitro lipid digestion and absorption models - Yue Xiao; Yanni Huang; Feiwu Long; Dongmei Yang; Yan Huang; Yuanyuan Han; Yanping Wu; Kai Zhong; Qian Bu; Hong Gao; Yina Huang (Food Chemistry, 2023)

Multi-color solid-state photoluminescence from orthogonally multi-stimuli-responsive organic molecule for advanced information storage and encryption - Qi Zhang; Li Yang; Yanfei Gao; Yanping Xiang; Hongjuan Li; Shiguo Sun; Yongqian Xu (Chemical Engineering Journal, 2023)

Melatonin Antagonizes Cytokinin Responses to Stimulate Root Growth in Arabidopsis - Yanping Wang; Jinzhu Li; Li Yang; Zhulong Chan (Journal of Plant Growth Regulation, 2023)

The development and future frontiers of global ecological restoration projects in the twenty-first century: a systematic review based on scientometrics - Xue Jiang; Yitao Sun; Yanping Qu; Houyuan Zeng; Jingtian Yang; Kaiyou Zhang; Lei Liu (Environmental Science and Pollution Research, 2023)

Characteristics of volatile organic compounds and secondary organic aerosol pollution in different functional areas of petrochemical industrial cities in Northwest China - Yanping Yang; Wenkai Guo; Jian Sun; Qiang Chen; Xianhong Meng; Lina Wang; Huijie Tao; Lili Yang (Science of The Total Environment, 2023)

Hormonal Profiling of Encapsulated and Nonencapsulated Rhizomes of Chinese Cymbidium in Different Storage Environments - Shuangbin Fu; Zhuang Zhou; Yanping Yang; Zhen Ying; Wan Xu (Journal of Plant Growth Regulation, 2023)

Underwater superoleophobic GO-PEI-SiO2-Hal quaternary sphere-rod nacre-inspired mesh by LBL self-assembly for high-efficiency oil-water separation - Xiaohua Tian; Sujun Tian; Lulu Wang; Yanping Yang; Ruilong Zhang; Jiangdong Dai; Jianming Pan (Applied Clay Science, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Advances in air pollution control for key industries in China during the 13th five-year plan - Xuecheng Wu; Yanping Yang; Yue Gong; Zhiwen Deng; Ying Wang; Weihong Wu; Chenghang Zheng; Yongxin Zhang (Journal of Environmental Sciences, 2023)

Advances in air pollution control for vessels in China - Yanping Yang; Yue Gong; Ying Wang; Xuecheng Wu; Zhiying Zhou; Weiguo Weng; Yongxin Zhang (Journal of Environmental Sciences, 2023)

Production of high affinity monoclonal antibody and development of indirect competitive chemiluminescence enzyme immunoassay for gentamicin residue in animal tissues - Peng Dai; Yan Zhang; Yanping Hong; Jianhua Xiong; Huaying Du; Luying Duan; Dan Wang; Yubo Wang; Weijie Deng; Bruce D. Hammock; Wuying Yang (Food Chemistry, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

In situ transformation of bismuth-containing precursors into ultrathin bismuth nanosheets for enhanced electrochemical CO2 reduction - Aihao Xu; Dong Wei; Xiangyu Chen; Taishun Yang; Yanping Huang; Huibing He; Jing Xu (Chemical Engineering Journal, 2023)

Citric Acid and Poly-glutamic Acid Promote the Phytoextraction of Cadmium and Lead in Solanum nigrum L. Grown in Compound Cd–Pb Contaminated Soils - Yu Wang; Weidong Duan; Chao Lv; Zhuangzhuang Wei; Yanping Zhu; Qi Yang; Ying Liu; Zhenguo Shen; Yan Xia; Kun Duan; Lingtong Quan (Bulletin of Environmental Contamination and Toxicology, 2023)

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Dual modification based on electrostatic repulsion of bentonite and SPR effect of Bi facilitate charge transfer of Bi2WO6 for antibiotics degradation - Tingting Zhu; Yanping Hou; Guofu Huang; Tian Fu; Jinhang Yang; Yutong Wang; Hanbing Zhang (Environmental Science and Pollution Research, 2022)

Genomic distribution of signal transducer and activator of transcription (STAT) family in colorectal cancer - Yanping Hu; Yifen Shen; Yang Zhao; Ying Tang; Chao Liu; Yongchun Gu; Tao Yang; Yihang Shen (Human Cell, 2022)

Molecular phylogeny and divergence time estimates for native giant clams (Cardiidae: Tridacninae) in the Asia-Pacific: Evidence from mitochondrial genomes and nuclear 18S rRNA genes - Haitao Ma; Dongmei Yu; Jun Li; Yanping Qin; Yang Zhang; Zhiming Xiang; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2022)
Giant clams are conspicuous bivalves that inhabit in coral reefs. Among the giant clams, eight species of subfamily Tridacninae are the most common in the Asia-Pacific. However, very little is known about their evolutionary history. Here, we determined the complete mitochondria genome of Hippopus porcellanus , which was 29,434 bp in size and contained 13 protein-coding genes, 2 rRNAs and 23 tRNAs. The A+T composition of protein-coding regions was 57.99%, and the AT composition of the 3 rd codon position was 59.33%, of which in agreement with the invertebrate bias favoring codons ending in A or T. Analysis of phylogenetic relationships according to the concatenated nucleotide data set containing 18S rRNA gene and 13 protein-coding genes, the phylogenetic relationship was analyzed by Maximum likelihood and Bayesian inference methods. The results showed that T. maxima was placed with the clade comprising T. noae , T. squamosa , and T. crocea , in which T. squamosa was highly similar to T. crocea and is consistent with the results of the previous studies using15 mitochondrial markers and nuclear 18S rRNA. Moreover, the inferred divergence time of Tridacnidae species is generally consistent with the fossil record of Tridacnidae. The divergence time of H. porcellanus and H. hippopus was about 10.64 Mya, this result is in agreement with the speculation that H. porcellanus also originated in Miocene. The availability of molecular phylogeny and divergence time estimation provides information genetic relationship of Tridacninae, which could be helpful to the ecological research and conservation of giant clams.

Impact of waste of COVID-19 protective equipment on the environment, animals and human health: a review - Sheng Yang; Yanping Cheng; Tong Liu; Shaoping Huang; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Chemistry Letters, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Practical research on improving nano majors students' social adaptability by quality development course - Yi Li; Shijun Xu; Cong Zeng; Yanping Yang (Nanotechnology for Environmental Engineering, 2022)

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

Development and application of a shaking table system - Chunhua Gao; Yanping Yang; Jieqiong Wang; Mengyuan Qin; Xiaobo Yuan (Arabian Journal of Geosciences, 2022)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Analyses of the circadian clock genes expression in whole embryos and maternal major tissues of mice - Ximei Cao; Yindi Yan; Xuguang Luo; Xinhua Yang; Huilin Cui; Yanping Yang; Hairong Li (Journal of Molecular Histology, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Molecular epidemiology and clinical characterization of human rhinoviruses circulating in Shanghai, 2012-2020 - Haixia Jiang; Tianyun Yang; Chunyi Yang; Yanping Lu; Zhigang Yi; Qin Zhang; Wei Wang (Archives of Virology, 2022)

Anisakidae parasitism activated immune response and induced liver fibrosis in wild anadromous Coilia nasus - Congping Ying; Xin Fang; Honglan Wang; Yanping Yang; Pao Xu; Kai Liu; Guojun Yin (Journal of Fish Biology, 2022)
Anisakidae nematode larvae is one of the most common parasites in wild anadromous Coilia nasus . This study aims to explore the mechanism of the C. nasus immune response to the parasitism of Anisakid nematode larvae. Results found that Anisakid nematode larvae parasitism caused liver injury as evidenced by histomorphology results as well as high levels of aminotransferase and aspertate aminotransferase. Furthermore, Anisakid nematode larvae parasitism induced an immune response in the host, which was characterized by the elevated populations of macrophages and neutrophils in the liver and head‐kidney in the Anisakidae‐infected group compared to the noninfected group. The expression of immunoglobulin IgM and IgD in the liver and head‐kidney was also increased in the Anisakidae‐infected group. The Anisakidae‐infected group showed higher activity of antioxidant enzymes catalase and superoxide dismutase, which indicates severe oxidative stress, and increased production of pro‐inflammatory cytokines, TNF‐α, IL‐6 as well as MCP‐1 in the liver compared with the noninfected group. As a result of inflammation, livers of hosts in the Anisakidae‐infected group showed fibrosis, and elevated expression of associated proteins including α‐smooth muscle actin, fibronectin, collagen type I and type III compared with the noninfected group. We demonstrated that Anisakid nematode larvae parasitism results in injury and fibrosis in the liver, and triggers immune cell infiltration and inflammation in the liver and head‐kidney of C. nasus . Altogether, the results provide a foundation for building an interaction between parasite and host, and will contribute to C. nasus population and fishery resource protection.

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

SARS-CoV-2 competes with host mRNAs for efficient translation by maintaining the mutations favorable for translation initiation - Yanping Zhang; Xiaojie Jin; Haiyan Wang; Yaoyao Miao; Xiaoping Yang; Wenqing Jiang; Bin Yin (Journal of Applied Genetics, 2022)

Characterization of a newly identified RNA segment derived from the genome of Sclerotinia sclerotiorum reovirus 1 - Jichun Jia; Fan Mu; Yanping Fu; Jiasen Cheng; Yang Lin; Daohong Jiang; Jiatao Xie (Archives of Virology, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Optimization of a Cable Support Strategy for Roadways in Coal Mines by Using the PSO Algorithm - Zhu Tang; Shuqing Li; Fei Huang; Junwei Yang; Fuling Yang; Yanping Zhu; Dangzheng Yang; Nan Wen (Geotechnical and Geological Engineering, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Characterization of a novel botoulivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Fan Mu; Jichun Jia; Yunxiang Xue; Daohong Jiang; Yanping Fu; Jiasen Cheng; Yang Lin; Jiatao Xie (Archives of Virology, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

A Significant Genetic Admixture in Farmed Populations of the Noble Scallop Chlamys nobilis Revealed by Microsatellite DNA Analysis in Southern China - Haitao Ma; Dongmei Yu; Shu Xiao; Yanping Qin; Yang Zhang; Jun Li; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2021)
The noble scallop, Chlamys nobilis , is an important bivalve mollusk with high commercial value and is usually farmed in the waters of southern China. To date, very little is known about the genetic diversity and population structure of C. nobilis . In this study, 10 microsatellite loci of four farmed C. nobilis populations were compared with one another and compared wild population in southern China. A total of 83 alleles were found. Surprisingly, the level of genetic diversity of the farmed C. nobilis populations was higher than that of the wild population. Although the population genetic of wild population was completely in the Hardy–Weinberg equilibrium, due to heterozygote deficiency, significant deviations from the Hardy–Weinberg equilibrium were found in all farmed populations, suggesting a genetic admixture caused by the mixing of seeds from various hatcheries. The Fst and AMOVA values showed significant genetic differences between wild and farmed populations. The Bayesian assignment also confirmed that genetic admixture was significant and widespread in artificial breeding of C. nobilis . Furthermore, the UPGMA tree topology and PCA demonstrated that the genetic diversity of wild population can be clearly distinguished from farmed populations. In a nutshell, the findings of this study not only fill the knowledge gaps in genetic diversity of wild and farmed C. nobilis populations, but also serve as a guide for maintaining the genetic diversity of C. nobilis in both farmed and wild populations.

Therapeutic efficacy of chitosan nanoparticles loaded with BCG-polysaccharide nucleic acid and ovalbumin on airway inflammation in asthmatic mice - Wentao Yang; Zhaohui Dong; Yujing Li; Yingying Zhang; Huanqin Fu; Yanping Xie (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

GAS5 knockdown suppresses inflammation and oxidative stress induced by oxidized low-density lipoprotein in macrophages by sponging miR-135a - Yunyan Zhang; Xianben Lu; Minjun Yang; Jiaolin Shangguan; Yanping Yin (Molecular and Cellular Biochemistry, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Formulation and Pharmacokinetic Evaluation of a Drug-in-Adhesive Patch for Transdermal Delivery of Koumine - Yanping Su; Wenxiang Lu; Xiaoling Fu; Ying Xu; Lixiang Ye; Jian Yang; Huihui Huang; Changxi Yu (AAPS PharmSciTech, 2020)

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Phytochemicals and inflammatory bowel disease: a review - Imam Hossen; Wu Hua; Luo Ting; Arshad Mehmood; Song Jingyi; Xu Duoxia; Cao Yanping; Wu Hongqing; Gao Zhipeng; Zhang Kaiqi; Yang Fang; Xiao Junsong (Critical Reviews in Food Science and Nutrition, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Microbial reduction of bromate: current status and prospects - Xinyue Lv; Dan Wang; Waheed Iqbal; Bo Yang; Yanping Mao (Biodegradation, 2019)

Digestive enzyme activity of the Japanese grenadier anchovy Coilia nasus during spawning migration: influence of the migration distance and the water temperature - Fengjiao Ma; Yanping Yang; Min Jiang; Denghua Yin; Kai Liu (Journal of Fish Biology, 2019)
In this study, we investigated the activity levels of two major digestive enzymes (pepsin and lipase) in the commercially important Japanese grenadier anchovy Coilia nasus during its upstream migration to analyse the digestive physiological responses to starvation and to analyse the influence of the water temperature on enzyme activity. Water temperature had a significant effect on pepsin activity, while long‐term starvation resulted in a significant decrease in pepsin activity. As starvation continued, however, a slight increase in pepsin activity between the Wuhu (440 river km) and Anqing (620 river km) regions may indicate that C. nasus had refeeding behaviour due to its large expenditure of energy reserves. In contrast, lipase activity was not significantly affected by the water temperature but the effect of fasting increased as much as 13% of lipase activity from the Chongming region (20 river km) to Anqing region, suggesting that the stored lipids of grenadier anchovy were mobilised to meet energy requirements of upstream migration activity and gonad development. Lipid mobilisation activated lipoprotein lipase (LPL; proteins with lipase activity) to hydrolyse triacylglycerides (TAG), which is the first step of lipid assimilation and obtained energy from fatty acids under fasting conditions. Therefore, the increased lipase activity is attributed mainly to the lipase that is involved in endogenous lipid hydrolysis. Grenadier anchovy appears to adapt to long‐term starvation during migration and the increased lipase activity may indicate a crucial effect on lipid metabolism. This study demonstrated that distinct alterations occur in pepsin and lipase activities during the spawning migration of grenadier anchovy due to exogenous nutrition and endogenous metabolism. Furthermore, it provides a basis for further research on the digestive physiology and energy metabolism in this species.

Cefquinome-Loaded Microsphere Formulations in Protection against Pneumonia with Klebsiella pneumonia Infection and Inflammatory Response in Rats - Shaoqi Qu; Cunchun Dai; Fenfang Yang; Tingting Huang; Zhihui Hao; Qihe Tang; Haixia Wang; Yanping Zhang (Pharmaceutical Research, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Active Biomonitoring of Metals with Cultured Anodonta woodiana: A Case Study in the Taihu Lake, China - Xiubao Chen; Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Clonal diversity of Ureaplasma species and its relationship with oligozoospermia and semen quality in Chinese infertile males - Ting Yang; Yanping Zou; Weili Zhou; Zhi Ruan; Yingying Kong; Yunheng Zhou; Jun Zhang; Xinyou Xie (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line - Gang Su; Wenke Yang; Wenbo Meng; Qionghui Wu; Yanping Luo; Xingming Ma; Shen Zhao; Xiaodong Xie; Guang-Qin Guo (Natural Product Research, 2018)

Colonization and Gut Flora Modulation of Lactobacillus kefiranofaciens ZW3 in the Intestinal Tract of Mice - Zhuqing Xing; Wei Tang; Ying Yang; Weitao Geng; Rizwan Ur Rehman; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Enhanced a novel β-agarase production in recombinant Escherichia coli BL21 (DE3) through induction mode optimization and glycerol feeding strategy - Zhuhua Chan; Xinglin Chen; Yanping Hou; Boliang Gao; Chungui Zhao; Suping Yang; Runying Zeng (Acta Oceanologica Sinica, 2018)

Mineral composition variation in the shells of freshwater mussel Anodonta woodiana at different growth stages - Xiubao Chen; Yanping Su; Hongbo Liu; Tao Jiang; Jian Yang (Invertebrate Reproduction & Development, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

Br/Cl, I/Cl and chlorine isotopic compositions of pore water in shallow sediments: implications for the fluid sources in the Dongsha area, northern South China Sea - Yanping Li; Shaoyong Jiang; Tao Yang (Acta Oceanologica Sinica, 2017)

Expression of lycopene biosynthesis genes fused in line with Shine-Dalgarno sequences improves the stress-tolerance of Lactococcus lactis - Xiangrong Dong; Yanping Wang; Fengyuan Yang; Shanshan Zhao; Bing Tian; Tao Li (Biotechnology Letters, 2017)

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans - Xiaoxiang Yang; Hui Cui; Jiasen Cheng; Jiatao Xie; Daohong Jiang; Tom Hsiang; Yanping Fu (Environmental Microbiology, 2016)
Summary Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .

Genetic diversity of gliadin in Secale cereale subsp. segetale from Xinjiang, China - Yonghe Che; Ming Dai; Yanping Yang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2016)

Effects of Calcium and Magnesium Ions on Acute Copper Toxicity to Glochidia and Early Juveniles of the Chinese Pond Mussel Anodonta woodiana - Hongbo Liu; Xiubao Chen; Yanping Su; Ik Joon Kang; Xuchun Qiu; Yohei Shimasaki; Yuji Oshima; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Molecular identification of Kiss/GPR54 and function analysis with mRNA expression profiles exposure to 17α-ethinylestradiol in rare minnow Gobiocypris rarus - Yanping Yang; Jiancao Gao; Cong Yuan; Yingying Zhang; Yongjing Guan; Zaizhao Wang (Molecular Biology Reports, 2016)

Impact of Biological Treatment Techniques on Perfluoroalkyl Acids Emissions in Municipal Sewage - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Long He; Jincan Shen; Zhifang Chai; Bo Yang; Yanping Wang (Water, Air, & Soil Pollution, 2016)

A Comprehensive Analysis of Carotenoid Cleavage Dioxygenases Genes in Solanum Lycopersicum - Yanping Wei; Hongjian Wan; Zhiming Wu; Rongqing Wang; Meiying Ruan; Qingjing Ye; Zhimiao Li; Guozhi Zhou; Zhuping Yao; Yuejian Yang (Plant Molecular Biology Reporter, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Detection of virus in CSF from the cases with meningoencephalitis by next-generation sequencing - Hongzhi Guan; Ao Shen; Xia Lv; Xunzhe Yang; Haitao Ren; Yanhuan Zhao; Yinxin Zhang; Yanping Gong; Peixiang Ni; Honglong Wu; Yicheng Zhu; Liying Cui (Journal of NeuroVirology, 2016)

Isolation of a new carboline alkaloid from Trigonostemon lii - Hongmei Yang; Yanping Luo; Hongmei Zhao; Jichun Wu; Yegao Chen (Natural Product Research, 2016)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Analysis of Bacterial Diversity During Acetic Acid Fermentation of Tianjin Duliu Aged Vinegar by 454 Pyrosequencing - Qian Peng; Yanping Yang; Yanyun Guo; Ye Han (Current Microbiology, 2015)

Morphological development and growth of the freshwater mussel Anodonta woodiana from early juvenile to adult - Xiubao Chen; Hongbo Liu; Yanping Su; Jian Yang (Invertebrate Reproduction & Development, 2015)

Brain differences in first-episode schizophrenia treated with quetiapine: a deformation-based morphometric study - Chunlan Yang; Shuicai Wu; Wangsheng Lu; Yanping Bai; Hongjian Gao (Psychopharmacology, 2015)

Molecular characterization of PXR and two sulfotransferases and hepatic transcripts of PXR, two sulfotransferases and CYP3A responsive to bisphenol A in rare minnow Gobiocypris rarus - Jiancao Gao; Yingying Zhang; Yanping Yang; Cong Yuan; Fang Qin; Shaozhen Liu; Yao Zheng; Zaizhao Wang (Molecular Biology Reports, 2014)

Orexin A attenuates the sleep-promoting effect of adenosine in the lateral hypothalamus of rats - Yanping Cun; Lin Tang; Jie Yan; Chao He; Yang Li; Zhian Hu; Jianxia Xia (Neuroscience Bulletin, 2014)

Diagnostic value of circulating microRNAs for hepatocellular carcinoma - Yanping Yang; Rui Zhu (Molecular Biology Reports, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Identification and characterization of two novel transcription units of porcine circovirus 2 - Zhangzhao Gao; Qinfang Dong; Yonghou Jiang; Tanja Opriessnig; Jingxiu Wang; Yanping Quan; Zongqi Yang (Virus Genes, 2013)

Soil Respiration and N2O Flux Response to UV-B Radiation and Straw Incorporation in a Soybean–Winter Wheat Rotation System - Zhenghua Hu; Hailing Cui; Shutao Chen; Shuanghe Shen; Hanmao Li; Yanping Yang; Cenzi Li (Water, Air, & Soil Pollution, 2013)

RETRACTED ARTICLE: Isolation and analysis of homoeologous genes encoding gibberellin 2-oxidase 3 isozymes in common wheat - QIUFANG CHEN; HUIYUAN YA; SHIMING LI; YANPING YANG; GUANGYONG QIN; XUELI AN; DAOWEN WANG; KUNPU ZHANG; ZHEN JIAO (Journal of Genetics, 2012)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

Metals and Metalloids in the Water–Bloom-Forming Cyanobacteria and Ambient Water from Nanquan Coast of Taihu Lake, China - Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2012)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Proteomics-based analysis of novel genes involved in response toward soybean mosaic virus infection - Hua Yang; Yanping Huang; Haijian Zhi; Deyue Yu (Molecular Biology Reports, 2011)

Single nucleotide polymorphism of FSHβ gene associated with reproductive traits in Japanese flounder (Paralichthys olivaceus) - Feng He; Haishen Wen; Dahui Yu; Jifang Li; Bao Shi; Caifang Chen; Jiaren Zhang; Guoxiong Jin; Xiaoyan Chen; Dan Shi; Yanping Yang (Journal of Ocean University of China, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

Contribution of bovine lactoferrin inter-lobe region to iron binding stability and antimicrobial activity against Staphylococcus aureus - Xuejing Bai; Da Teng; Zigang Tian; Yanping Zhu; Yalin Yang; Jianhua Wang (BioMetals, 2010)

Antifungal substances produced by Penicillium oxalicum strain PY-1—potential antibiotics against plant pathogenic fungi - Liping Yang; Jiatao Xie; Daohong Jiang; Yanping Fu; Guoqing Li; Fangcan Lin (World Journal of Microbiology and Biotechnology, 2008)

Overexpression of SBPase enhances photosynthesis against high temperature stress in transgenic rice plants - Lingling Feng; Kun Wang; Yang Li; Yanping Tan; Jin Kong; Hui Li; Yangsheng Li; Yingguo Zhu (Plant Cell Reports, 2007)

Genomic comparison of Yersinia pestis and Yersinia pseudotuberculosis by combination of suppression subtractive hybridization and DNA microarray - Xiaoyi Wang; Dongsheng Zhou; Long Qin; Erhei Dai; Jianguo Zhang; Yanping Han; Zhaobiao Guo; Yajun Song; Zongmin Du; Jin Wang; Jun Wang; Ruifu Yang (Archives of Microbiology, 2006)

The Influence of Mycobacterium tuberculosis Sigma Factors on the Promotion Efficiency of ptpAt Promoter in Mycobacterium smegmatis - Jianqiang Lei; Hongmei Zhang; Chunlan Wu; Xiaolei Wang; Yanping Yang; Xuelian Zhang; Yishu Huang; Honghai Wang (Current Microbiology, 2005)

Real-time quantitative assay of telomerase activity using the duplex scorpion primer - Yanping Huang; Deming Kong; Yi Yang; Ruifang Niu; Hanxi Shen; Huaifeng Mi (Biotechnology Letters, 2004)